Males prefer virgin females, even if parasitized, in the terrestrial isopod Armadillidium vulgare. Issue 6 (21st February 2018) - Fortin, Margot; Debenest, Catherine; Souty‐Grosset, Catherine; Richard, Freddie‐Jeanne
Abstract: In many species, males increase their reproductive success by choosing high‐quality females. In natural populations, they interact with both virgin and mated females, which can store sperm in their spermatheca. Therefore, males elaborate strategies to avoid sperm competition. In the terrestrial isopod Armadillidium vulgare, females can store sperm and produce several clutches. Moreover, this species can be parasitized by Wolbachia, which feminizes genetic males, transforming them into functional females. Our study compared attractiveness and mate choice when a male is exposed to both virgin and experienced females (i.e., females who have produced offspring and rested for 6 months), with or without Wolbachia . Our results revealed that males are more attracted to virgin females than experienced females, even if these virgin females are parasitized. Moreover, the chemical analysis highlighted different odors in females according to their reproductive and infection ( Wolbachia‐ free or vertically Wolbachia ‐infected) status. Males attempted copulation more frequently and for longer with virgin females, even if Wolbachia ‐infected, while experienced females refused further copulation. The evolutionary consequences of both male choice and female resistance on their fitness are discussed in this study. Abstract : In the terrestrial isopod Armadillidium vulgare, infected with the feminizing bacteria Wolbachia, females can store sperm from previous matings. We investigated male mate choice when a male can choose between virgin and experienced (i.e., used 6 months after releasing their offspring) females. Our results suggest that males are able to recognize and prefer virgin females, even if females are infected with Wolbachia, whereas experienced females refused new mating.